Current Cancer Scenario and Analysis from Kolasib District of Mizoram, Northeastern India - Ralte, Lalhmangaihzuali; Lalramliana, C; Solo, Beihrosa (Journal of Neonatal Surgery, 2025)
This study, conducted from 2015 to 2020, focused on cancer patients in the Kolasib District of Mizoram, Northeast India. Over six years, 705 cases of cancer were recorded, encompassing 25 different types. Among these, oesophageal cancer emerged as the most prevalent, accounting for 129 cases (18.30%), followed by lung cancer, which comprised 106 cases (15.04%). Cervical and stomach cancers shared the third position, each contributing 66 cases (9.36%).The study also highlighted gender disparities, revealing a higher incidence of cancer among females compared to males. Additionally, the age group most affected was 50-59 years, followed by individuals aged 60-69 years, with minimal cases reported in individuals below 29 years. Despite ongoing efforts by the government and healthcare workers, the cancer incidence rate in the region remains high, underscoring the need for further research in this area.